Myocardial ischemia in neonate with perinatal asphyxia: Electrocardiographic, echocardiographic and enzymatic correlation - Merchant, Saira; Meshram, Rajkumar M; Khairnar, Devendra (Indian Journal of Child Health, 2016)
Objective: The objective of this study is to evaluate the presence and severity of cardiac involvement in asphyxiated neonates and to established which clinical and laboratory parameters (electrocardiogram [ECG], echocardiography [ECHO], and cardiac enzyme) are reliable predictors of myocardial ischemia. Design: Nested case–control study. Setting: Neonatology unit of tertiary care institute. Materials and Methods: The study group consist of 90 term neonates who had APGAR score 9 at 5 min as controls. On the 2nd day of life (between 24 and 36 h), all neonate underwentECG, ECHO, and enzyme estimation (CK-MB). Result: The cases were divided into three groups according to SARNAT scale andGroup I consist 25, Group II - 54, and Group - III, 11 neonates. The mean gestational age was 36.97±0.35 and 37.12±0.46 week for cases and controls respectively while mean birth weight was 2.79±0.36 kg and 2.68±0.76 kg for cases and controls, respectively. ECG changes were present in 70 (77.7%) of cases. ECG changes of Grade 3 and 4 were present in only Group III neonates and all neonates with Grade 4 changes were died in 1st week of life. Fractional shortening (FS) decreased progressively from Group I to Group III (p